Radically Truncated Clauses in Hungarian and Beyond: Evidence for the Fine Structure of the Minimal VP. (4th May 2021) - Halm, Tamás
Abstract: This article explores the syntax of radically truncated clauses in colloquial Hungarian. I argue that radically truncated clauses arise when, in informal speech situations and under time pressure, the derivation is terminated prematurely, at the VP level, and the bare VP (lacking any of the higher functional projections) is sent to spellout (PF) and semantic interpretation (LF). Due to their radically truncated nature, such clauses provide us a unique window through which it becomes possible to explore the fine structure of the minimal VP in itself. I show that radically‐truncated‐clause data are highly relevant to various theoretical questions, such as the head–complement branching order, the adjunction analysis of topicalization and quantification, and the split‐DP proposal. I argue that observations about radically truncated clauses support the availability of OV as a nonderived, basic word order, that they are in line with the adjunction analysis of topicalization and quantifier raising, and that they corroborate the split‐DP analysis of arguments. The discussion is supported with evidence from corpus data and with rigorous statistical analysis of grammaticality‐judgment‐survey results.